Passion fruit (Passiflora edulis Sims) by-products as a source of bioactive compounds for non-communicable disease prevention: extraction methods and mechanisms of action: a systematic review - Weyya, Getu; Belay, Abera; Tadesse, Eneyew (Frontiers in Nutrition, 2024)
The review titled Passion fruit by-products as a source of bioactive compounds for noncommunicable disease prevention: extraction methods and mechanisms provide valuable insights into the health benefits and industrial applications of passion fruit waste. Passion fruits are a tropical and subtropical vine species, which produces edible fruits. Many food product types can be made from passion fruits. However, during passion fruit processing, large amounts of waste are released in to the environment. This review focuses on extraction methods of bioactive compounds from passion fruit by-products such as leaves, peels, seeds, and bagasse. Unlike previous reviews, this comprehensive article explores the potential health benefits of multiple passion fruit waste products. It also highlights the importance of sustainable and green extraction methods, which have gained attention due to environmental concerns. Additionally, it examines the possible applications of these extracts for industrial goods such as food additives, colorants, nutraceuticals, natural antioxidants, and antimicrobial agents. By shedding light on these aspects, this review encourages further research and innovation in utilization of passion fruit waste as a source of bioactive compounds for non-communicable disease prevention and their mechanisms of action. This can advance the circular economy. Overall, it contributes new information emphasizing the potential of passion fruit by-products as a source of bioactive, and the findings have implications for the scientific community and industry, promoting a deeper understanding of the health benefits and sustainable practices associated with passion fruit waste utilization.